Efficiency of Pollination with some pollinizers in improving fruit set of Syrian olive cultivar "Khoderi" (Latakia University Journal -Biological Sciences Series, 2020)
The research was conducted in 2017 and 2019 seasons at Bouka center for research and plant production, Latakia, Syria in order to evaluate the efficiency of some local and imported olive cultivars (Dermlali, Coratina, French Picholine and Frantoio) as pollinizers in improving fruit set of autochthonous olive cultivar "Khoderi". Depending on seasons, "Khoderi" had moderate to high ovary abortion ratio. Significant correlation was found between number of flowers per inflorescence and the number of flowers with ovary abortion in 2019 season only. All studied cultivars had good pollen germinability. Self- incompatibility of "Khoderi" was partial to severe depending on study season. "Coratina" and "Dermlali" were efficient pollinizers for "Khoderi ", while "Picholine" and "Frantoio" weren’t. The overall results indicate that it is possible to improve fruit set of "khoderi" by planting it in mixed orchards with "Coratina" and "Dermlali". تم تنفيذ البحث خلال الموسمين 2017 و 2019 في مركز بوقا للبحوث والإنتاج النباتي، اللاذقية، سورية، بهدف تقييم فعالية بعض الأصناف المحلية والمدخلة (درملالي، كوراتينا، بيشولين فرنسي، فرانتويو) في تحسين العقد لصنف الزيتون المحلي "خضيري". أظهرت النتائج تمتع الصنف "خضيري" بنسبة متوسطة إلى عالية من إجهاض المبايض تبعا لعام الدراسة، وقد وجد ارتباط معنوي بين عدد الأزهار في النورة وعدد الأزهار المجهضة في موسم 2019 فقط. تمتعت جميع الأصناف المدروسة بنسبة جيدة من إنبات حبوب الطلع. تراوح عدم التوافق الذاتي للصنف "خضيري" بين جزئي وشديد تبعا لعام الدراسة. كان الصنفان "درملالي" و "كوراتينا" ملقحين فعالين، في حين لم يكن الصنفان "بيشولين" الفرنسي و "فرانتويو" متوافقين مع الصنف "خضيري". تشير مجمل النتائج لإمكانية تحسين عقد ثمار الصنف "خضيري" بزراعته بشكل مختلط مع الصنف "درملالي" و "كوراتينا".